Perencanaan Instalasi Pengolahan Air Minum di Kecamatan Pangalengan, Kabupaten Bandung - Muhamad Firqi Ramadhan; Etih Hartati (Jurnal Serambi Engineering, 2024)
The Sustainable Development Goals (SDGs), point 6, has the objective of ensuring access to clean water and sanitation. The planning of a drinking water treatment plant is an essential component of achieving Target 6.1, which aims to provide safe and affordable drinking water for all by 2030. However, the Pangalengan subdistrict in Bandung Regency is confronted with a significant challenge, as 56.67% of cattle farmers are engaged in the discharge of livestock waste into the Cisangkuy River. It is therefore imperative to plan the construction of a drinking water treatment plant in the Pangalengan subdistrict. The research method commences with a comparison of the results of raw water tests conducted on the Cisangkuy River, which are then contrasted with the stipulations set forth in Health Minister Regulation No. 2 of 2023. Subsequently, a population projection is conducted in order to ascertain the projected water demand. The projected water demand is 371.92 liters per second in 2032. Subsequently, the selection of treatment units is conducted using the Likert scale method. The analysis yielded the conclusion that the quality standards are exceeded by the parameters turbidity and coliform. The alternative units employed are the intake, barscreen, coagulation and flocculation, sedimentation, filtration, disinfection, and reservoir units.